Information Management and Pricing in Platform Markets - Jullien, Bruno; Pavan, Alessandro (Review of Economic Studies, 2019)
Abstract We study platform markets in which the information about users’ preferences is dispersed. First, we show how the dispersion of information introduces idiosyncratic uncertainty about participation decisions and how the latter shapes the elasticity of the demands and the equilibrium prices. We then study the effects on profits, consumer surplus, and welfare of platform design, blogs, forums, conferences, advertising campaigns, post-launch disclosures, and other information management policies affecting the agents’ ability to predict participation decisions on the other side of the market.